Phát hiện nước ngọt dưới đất ngoài biển bằng phương pháp ảnh điện (ĐSĐ 2D) - Bàng, Nguyễn Hồng (Vietnam Journal of Earth Sciences, 2009)
Detection of submarine fresh groundwater by electrical imaging method